Phytochemical profiling and anti-aging activities of Euphorbia retusa extract: In silico and in vitro studies - Abdelbaset M. Elgamal; Mohamed A. El Raey; Ahmed Gaara; Mohamed A.O. Abdelfattah; Mansour Sobeh (Arabian Journal of Chemistry, 2021)
In this work, the phytochemical profiling of Euphorbia retusa aerial parts by HPLC-PDA-MS/MS revealed 21 secondary metabolites including phenolic acids, flavonoids, and their glycoside derivatives. The chemical structures of four isolated compounds (Esculetin, quercetin 3-O-β-D-glucuronide, kaempferol 3-O-β-D-glucuronide, and kaempferol 3-O-β-D-glucoside) were elucidated using mass spectrometry, 1H, and 13C NMR spectroscopy. Among the isolated compounds, kaempferol-3-O-glucuronide and esculetin were identified for the first time from the plant. An in silico molecular docking study showed the high potential of the identified compounds in the extract to bind to the active sites of four enzymes crucially involved in skin remodeling and aging processes. The in vitro assay confirmed the docking results against collagenase, elastase, hyaluronidase, and tyrosinase enzymes respectively. Among the four isolated compounds, kaempferol 3-O-glucoside was the highest active compound against the aforementioned enzymes. Moreover, the extract showed substantial antioxidant activity in DPPH assay. In conclusion, E. retusa is a substantial source for bioactive secondary metabolites with potential application in aging.